DIFFERENCE OF USING ‘URF ON GOLD JEWELLERY OF ZAKAH : A STUDY IN SELANGOR AND MALACCA - Nor Mohd Faisal bin Md Ariffin (At-Taradhi Jurnal Studi Ekonomi, 2016)
Urf is an additional source for Masadir al-Tasyrik (Syarak main source) and a method used by fuqaha to determine law of matters that undisclosed by nas for qat’i or been confrmed yet. It involves variety of aspects especially in Islam. This purpose of writing is to elaborate on zakat that have connection on gold that used to be clothes or jewellery by woman. The discussion is based on many Ulama’s opinions on real law of using gold as jewellery from zakat’s view. Focus and emphasis will be given to conduct a research on urf’s fxed rate for Malacca and Selangor at current time being. What is the most attention is the zakat on jewellery is different from other type of gold because one have their own ‘illah.Analysis shows that majority Ulama’ including al-Syaf’i which followed by majority Malaysian had decided a law that it is not compulsory to pay zakat on jewellery that wear by woman to celebrate their rights as written in al-Hadith. But,permissibility given by Ulama’ is strict on particular rate that been decided by Urf followed he rate made by current Ulama. Research also proved that there are many difference in rate of Urf based on state practise especially in Selangor and Malacca that need to be pay attention by specifc person in order to avoid curiosity in community. This issue appears to be discussed further across the diversity of fqh created and triggered by Ulama as a reference of law by ummah, towards arising current problems and never ended. Method used by MAIS and PZM act as indicator to the rate of using current gold and will be given priority as outcomes for this research to answer the questions about difference between both state.Keywords : ‘urf, zakah, gold jewellery,